The Influence of Socioeconomic Status on Psychological Distress in Canadian Adults With ADD/ADHD. Issue 9 (July 2019) - Pond, Emily; Fowler, Ken; Hesson, Jacqueline
Objective: The primary purpose of this study was to examine the relationship between socioeconomic status (SES) and psychological distress in individuals self-reporting a diagnosis of attention deficit disorder (ADD)/ADHD.Method: This correlational study encompasses cross-sectional data from 488 male and female adults (20-64 years) who reported that they have been diagnosed with ADD/ADHD. Psychological distress was measured with the Kessler Psychological Distress Scale (K10).Results: Adults with ADD/ADHD and high incomes have significantly lower K10 scores than Canadians with ADD/ADHD and low incomes. Income, but not education, was significant in predicting psychological distress among the sample. Canadian adults with ADD/ADHD have an increased risk for developing psychological distress and comorbid psychiatric disorders.Conclusion: The findings suggest that negative outcomes associated with ADD/ADHD are not necessarily pervasive. High income may serve as a protective factor for psychological distress among adults with ADD/ADHD.